The Judgment of the Italian Constitutional Court on State Immunity in Cases of Serious Violations of Human Rights or Humanitarian Law: a tentative analysis under international law - Pasquale De Sena (Sequência: Estudos Juridicos e Politicos)
http://dx.doi.org/10.5007/2177-7055.2016v37n74p97